THE DYNAMICS OF HUMAN RELATIONSHIP: A NARRATIVE COMPARISON BETWEEN 'HILLS LIKE WHITE ELEPHANTS' AND 'DEAD STARS' - Saputra, Taufan; Priyawan, Pepen; Pauji, Resa Restu (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This research analyzes two short stories,